2013
DOI: 10.1063/1.4772947
|View full text |Cite
|
Sign up to set email alerts
|

Donor ionization in size controlled silicon nanocrystals: The transition from defect passivation to free electron generation

Abstract: We studied the photoluminescence spectra of silicon and phosphorus co-implanted silica thin films on (100) silicon substrates as a function of isothermal annealing time. The rapid phase segregation, formation, and growth dynamics of intrinsic silicon nanocrystals are observed, in the first 600 s of rapid thermal processing, using dark field mode X-TEM. For short annealing times, when the nanocrystal size distribution exhibits a relatively small mean diameter, formation in the presence of phosphorus yields an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…3 , the dependence of the PL spectra on the P-concentration in SRO:P and SRON:P is demonstrated. Here, all samples are H 2 -passivated and hence only the PL-quenching effect of P-incorporation is visible, not the PL-enhancement often observed for low P-concentrations and associated to dangling bond passivation by P [ 42 ]. Up to the level of ≈0.6 atom % P the PL intensity drops by less than 40% without any significant peak shift.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , the dependence of the PL spectra on the P-concentration in SRO:P and SRON:P is demonstrated. Here, all samples are H 2 -passivated and hence only the PL-quenching effect of P-incorporation is visible, not the PL-enhancement often observed for low P-concentrations and associated to dangling bond passivation by P [ 42 ]. Up to the level of ≈0.6 atom % P the PL intensity drops by less than 40% without any significant peak shift.…”
Section: Resultsmentioning
confidence: 99%
“…The TT-results are presented for both H 2 -passivated and unpassivated states without distinctive differences, but one remark concerning the interaction of Si-doping and hydrogen shall be made: While P in the Si NC system is known to passivate dangling bonds (DBs) at the Si/SiO 2 interface [ 7 , 42 ] similar to a post-annealing in H 2 , hydrogen treatments have also been shown to deactivate P-donors and B-acceptors in heavily doped Si nanowires [ 47 ] and in the bulk [ 48 50 ]. However, this type of dopant passivation solely relies on very reactive atomic hydrogen (rather than molecular H 2 gas) and requires much lower temperatures of 100–150 °C to be efficient.…”
Section: Resultsmentioning
confidence: 99%
“…Crowe et al also reported a transition from defect passivation by P atoms to free carrier generation by P donors as the increase of rapid thermal annealing time during the Si-NCs growth when the other conditions were kept unchanged. 35 Charge number in Figs. 6(b) and 6(c) is also calculated, which is þ1.3 e and þ1.2 e, respectively.…”
Section: Figures 1(a) and 1(b)mentioning
confidence: 99%
“…Interaction of Si-NCs with Er ions has attracted a lot of attention due to the possibility of operating in the telecommunications band around 1.5 µm. Recent studies have shown that phosphorus doping can result in either a quenching or an enhancement of the Si-NC's PL, depending on the dopant concentration and NC sizes [28,35]. Crowe et al [35] suggested the existence of competing pathways for the donor electron, which depend strongly on the NC size.…”
Section: Properties and Characterizationmentioning
confidence: 99%
“…Recent studies have shown that phosphorus doping can result in either a quenching or an enhancement of the Si-NC's PL, depending on the dopant concentration and NC sizes [28,35]. Crowe et al [35] suggested the existence of competing pathways for the donor electron, which depend strongly on the NC size. For relatively small NCs, the tendency of phosphorus to accumulate at the nanocrystal-oxide interface results in a passivation of dangling bond type defects as evidenced by an enhancement of the integrated intensity and corresponding blue-shift of the emission peak.…”
Section: Properties and Characterizationmentioning
confidence: 99%